Witwickiego interpretacja Platona Objaśnienie do Państwa - Nieć, Mateusz (Wydawnictwo Uniwersytetu Wrocławskiego, 2013)
Who is Witwicki? Władysław Witwicki 1878–1948 is a psychologist and a philosopher, a man of Renaissance painter, sculptor, writer, a historian of arts as well as a famous translator of Plato. He translated almost all works by Plato, he wrote 3780 pages about Plato. I analyze only Commentary by Witwicki, not the political treatise State by Plato. According to Witwicki, State is a treatise on modern politics and history. Plato became a pretext to analyze the Third Reich and the Soviet Union, and, in fact, Poland in 1948. Witwicki describes Stalinizm, a left totalitarian political system as a philosopher and a psychologist. He writes short sentences, often single words, he expresses emotions, not just cold views of a scientist.
Keywords: political theory; political psychology; totalitarianism; Stalinism; antique-modern; propaganda